The Effect of Investment, Export-Import, and Inflation Level on Economic Growth in Indonesia from The Perspective of Islamic Economics in 2004-2024 with The Vector Error Correction Model Approach - Dewi, Anisa Sukma; Supriyaningsih, Okta; Qurrahman, Taufiq (Manunggal Halim Jaya, 2025)
This study aims to analyze the influence of investment, export-import, and inflation rate on economic growth in Indonesia from the perspective of Islamic economics during the period 2004–2024. The Vector Error Correction Model (VECM) identifies short-term and long-term relationships among these variables. The data employed are annual secondary data from various official sources, such as the Central Bureau of Statistics and Bank Indonesia. The results indicate that, in the long term, investment and exports have a significant positive effect on economic growth, while inflation has a negative impact. In the short term, the relationships among these variables demonstrate complex dynamics, yet remain consistent with Islamic economic theory, which emphasizes stability, justice, and sustainable growth. This study provides important implications for macroeconomic policies aligned with sharia principles, particularly in efforts to achieve inclusive and equitable economic development in Indonesia.